PERBEDAAN BAHASA SISWA LAKI-LAKI DAN SISWA PEREMPUAN: SEBUAH STUDI KASUS DI KELAS V SDN 09 AIR TAWAR BARAT PADANG SUMATERA BARAT - Amri, Zul (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2009)
Male and female are said to speak differently in any communities. Many studies have made use of oral discourse as the source of the data and it is very rare found that the studies make use of written discources. This study is based on the students writing entitled â€œExperience during Vacationâ€. They are the fifth grade of 09 Elementary School Air Tawar Barat Padang. After analyzing their writings, it is found that female students produce more words, more verbs, more sentences (verbal or nominal and simple or embedded) compared to male students. In addition, female students produce less mistakes in using capital letter and other mechanical matters. The male students, on the other hand, produce less words, less verbs, less sentences (verbal or nominal and simple or embedded) compared to female students. In addition, male students produce more mistakes in using capital letter and other mechanical matters. One interesting thing is that even though male students produce less verbs in numbers, they have more various verbs compared to female students. Many female students use the same verbs as others and some use the same verbs repeatedly in their writings. The male students did not repeat the use of the same words very often.Â